2014
DOI: 10.5194/adgeo-39-89-2014
|View full text |Cite
|
Sign up to set email alerts
|

Long term evolution of a dam reservoir subjected to regular flushing events

Abstract: Abstract. An analysis of the long term morphological evolution of the Génissiat reservoir (France) is provided. First, a methodology for bathymetric data processing and reservoir sediment volume budget calculation is described. An estimation of global uncertainties in volume calculation is proposed. The reservoir bathymetric budget for several dam flushing events and interflush periods is presented, showing the global decrease of deposited sediment volume with time. The spatial dynamics of the reservoir subrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
0
10
0
3
Order By: Relevance
“…Finally, we calculated net change in sediment volume as: normalΔVj=Dj0.25emnormalΔAj where Δ A j is the cross‐sectional area difference between S i 1 and S i 2 for the j th CS and Dj=(),12Lj1+12Lj, with L j the longitudinal distance between the j th and ( j + 1)th CSs (Guertault et al , ). In cases where L j − 1 or L j were not defined, we considered Dj=12Lj or Dj=12Lj1 respectively.The uncertainty in sediment volumes due to transversal interpolation, smoothing and systematic bias is: ut,j=Dj0.25emEt,j Following Guertault et al (), we calculated the uncertainty in sediment volume due to the longitudinal interpolation between CSs. When the channel geometry is very different between consecutive CSs, the hypothesis of a constant evolution of sediment volume can be questioned.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we calculated net change in sediment volume as: normalΔVj=Dj0.25emnormalΔAj where Δ A j is the cross‐sectional area difference between S i 1 and S i 2 for the j th CS and Dj=(),12Lj1+12Lj, with L j the longitudinal distance between the j th and ( j + 1)th CSs (Guertault et al , ). In cases where L j − 1 or L j were not defined, we considered Dj=12Lj or Dj=12Lj1 respectively.The uncertainty in sediment volumes due to transversal interpolation, smoothing and systematic bias is: ut,j=Dj0.25emEt,j Following Guertault et al (), we calculated the uncertainty in sediment volume due to the longitudinal interpolation between CSs. When the channel geometry is very different between consecutive CSs, the hypothesis of a constant evolution of sediment volume can be questioned.…”
Section: Methodsmentioning
confidence: 99%
“…Large sedimentation occurred in the reservoir, and the storage loss by 2012 was estimated to be 36% of the initial storage capacity (Guertault et al. ). Comparison between the 1954 and 2011 longitudinal profiles showed that the upstream portion of the reservoir has been affected by bed incision, caused by the reduction of sediment transport due to upstream dams, and gravel mining activities performed from the 1970s to the 1990s (Figure a).…”
Section: The Génissiat Dam Reservoirmentioning
confidence: 99%
“…However, this last objective has not always been met, as the long‐term sediment budget of the Génissiat Reservoir showed that half of the sediment accumulation occurred during flushing operations of upstream dams (Guertault et al. ).…”
Section: The Génissiat Dam Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they have been successfully used to understand and reproduce to some extent complex physical processes that occur in nature, and have contributed significantly in hydraulic construction designs, they are relatively costly and time consuming [12]. More recently photogrammetry-based surveys using unmanned aerial systems have been used to evaluate flushed sediments [13][14][15]. Moreover, such techniques can only compute the amount of flushed sediments only when the reservoir is dry (i.e., empty), and subsequent images are necessary to compute the Digital Elevation Models (DEMs) of difference, from which the flushing efficiencies may be computed.…”
Section: Introductionmentioning
confidence: 99%